(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Employee Engagement is one of the vital approaches to improve the quality and productivity in any enterprise. Employee engagement is not a replacement for management nor is it the final word in quality improvement. It is a means to bettermeet the organizations goals for quality and productivity at all levels of an organisation. Employee engagement, therefore, pushes up the level of commitment, involvement and dedication that an employee has towards the organisation. The concept of employee engagement overlaps with the concept of commitment and organisational citizenship behaviour to a large extent but is different conceptually. The latter two concepts are uni-directional but engagement is a two-way concept- organisation work hard to engage their employees and the employees in turn decide on the level of engagement they would offer their employers. The present research paper focusses on the Employee engagement practices incorporated in Banking sector, since the banking sector plays a crucial role in the revenue generation under the service industry it is important to study the factors influencing to contribute more revenue as part of which from the literatures we understood that in recent years the employee engagement is the major contributing factor for the improvement of overall performance of the organization, hence, the study is conducted to explore and through light on the comparison between the public and private sector banks in incorporating the employee engagement practices.